(untitled) (Sains Humanika, 2012)
The study tries to explore the practice of instructional leadership and the attitude towards change among the principals of Technical and Vocational Schools in the state of Pahang. This research based on the instructional leadership model by Hallinger (2000) & Murphy (1990) and the attitude towards change based on the model of Dunham et al. (1989) ; Maio & Haddock (2009). Thus this article will discuss on four dimensions of instructional leadership practices, being i) define and establish school goals, ii) manage instructional program, iii) promote learning environment and iv) create friendly and cooperative school environment and three dimensions of attitude towards change focuses in i) cognitive, ii) affective and iii) behavioural based on the perception of 60 respondents (6 principals and 54 teachers). Findings of the study indicate that principals in Technical and Vocational Schools in the State of Pahang practice as instructional leaders were proved to be at high level and it is also found that they possess positive attitude towards organizational change. The findings using multiple regression shows that two out four dimensions of instructional leadership practices (define and establish school goals & create friendly and cooperative school environment) contributed 64.5% to the attitude towards change among the principals in Technical and Vocational Schools. This findings imply the need to enhance the practices as instructional leadership and attitude towards change of the Technical and Vocational School principals’ for the good to the schools in Pahang and throughout Malaysia.